2010
DOI: 10.1097/acm.0b013e3181cccdc4
|View full text |Cite
|
Sign up to set email alerts
|

Required vs. Elective Research and In-Depth Scholarship Programs in the Medical Student Curriculum

Abstract: The ability to understand and integrate new knowledge into clinical practice is a necessary quality of good physicians. Student participation in in-depth scholarship could enhance this skill in physicians while also creating a larger cadre of physician-scientists prepared to advance the field of medicine. However, because no definitive data exist demonstrating that in-depth scholarship in medical school leads to improved patient care or to productive academic careers, whether such scholarship should be require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 9 publications
2
78
0
3
Order By: Relevance
“…A required school-wide student research program is demanding in terms of resources, and full awareness of potential benefits and challenges is essential. While such programs have multiple potential educational benefits (short term and intermediate outcomes), the evidence that student research alone translates into improved patient care is still lacking 27 . Thus, the decision to require or not to require a research project for all students in a Pharm.D.…”
Section: Criticalmentioning
confidence: 99%
See 1 more Smart Citation
“…A required school-wide student research program is demanding in terms of resources, and full awareness of potential benefits and challenges is essential. While such programs have multiple potential educational benefits (short term and intermediate outcomes), the evidence that student research alone translates into improved patient care is still lacking 27 . Thus, the decision to require or not to require a research project for all students in a Pharm.D.…”
Section: Criticalmentioning
confidence: 99%
“…Moreover, previous experiences have shown that while highly enthusiastic, only few students seem to have the confidence and the ability to choose and maintain a research area early in their training 27,41,40 . Other challenges include difficulties in resolving a poor faculty-student match, midway changes of interest and the challenge to manage multiple academic demands, especially during the didactic courses of the initial years.…”
mentioning
confidence: 99%
“…Likewise, in addition to being able to solve clinical problems, students must work as researchers to enable them to be leaders in the healthcare community. 16 To achieve this goal, a curriculum supported by educational programs that help students develop critical analysis, resolve problems and manage people is fundamental.…”
Section: 13mentioning
confidence: 99%
“…Also, different universities have different courses regarding to research activities in the United States [9][10][11].…”
Section: Research Opportunitiesmentioning
confidence: 99%